Working with Substance: Actor-Network Theory and the Modal Weight of the Material. - McGrail, Robert (Techné: Research in Philosophy & Technology)
The article reports on the materials and designs of the actor-network theory (ANT). It also presents various ways of thinking such as ontological holism, nominalism or localism, and constructivism. Moreover, the author discusses the ANT's objects and subjects whether they are the different, the same or the local. Images of sample materials are also presented.